Varför har Haparanda lägst valdeltagande i Sverige? : En jämförande studie av kontextuella och individuella faktorer - Brännström, Laura (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2022)
In a representative democracy, voting in the general elections is a democratic right and turnout is an important indicator of whether the democratic system is doing well or whether there is a distrust of a political system. Sweden generally has a high voter turnout in the general elections, but Haparanda municipality stands out with by far the lowest voter turnout in the country. A low turnout in the general elections can lead to poorer representativeness and lead to legitimacy problems for political decision-making. The essay examines known contextual factors that, ac- cording to election research, explain low turnout in Haparanda. Furthermore, a comparison is made with Norrbotten's municipalities and Swedish border municipalities with the aim of find- ing if there is any clear indicator that can explain the low turnout. The comparison shows that Haparanda has one of the lowest average disposable incomes and a clearly higher proportion of foreign-born citizens than the other compared municipalities. Therefore, a comparison is also made of the voter turnout between Haparanda and other municipalities with an equal proportion of foreign born. The two indicators foreign-born citizens and disposable income are contextual factors that, according to previous research, affect voter turnout in a negative direction and that give Haparanda an uphill battle in the coming election year unless targeted investments are made to increase voter turnout in the municipality with Sweden's lowest voter turnout. I en representativ demokrati är röstning i de allmänna valen en demokratisk rättighet och val- deltagande en viktig indikator för huruvida det demokratiska systemet mår bra eller om det förekommer en misstro till ett politiskt system. Sverige har generellt ett högt valdeltagande i de allmänna valen, men Haparanda kommun utmärker sig med det i särklass lägsta valdeltagandet i landet. Ett lågt deltagande i de allmänna valen kan leda till sämre representativitet och leda till legitimitetsproblem för politiskt ...